Review: Pengembangan Agro – Ekowisata di Wilayah Pesisir Utara Jatim pasca Covid-19 (Perspektif Pengelolaan Sumberdaya Manusia) - Ali, Mukti; Soedarto, Teguh (Politeknik Negeri Sambas, 2022)
The impact of stopping and restricting social activities as well as travel restrictions is a decrease in the number of visits to the agro-ecotourism industry. The qualitative descriptive method is based on literature studies from journals, books, and articles on agro-ecotourism and how to recover it during the Covid-19 pandemic era. Various efforts have been made by managers, as well as several other stakeholders, to be a solution for developing agro-ecotourism after the Covid-19 pandemic. Alternative solutions that can be implemented, among others: (1) Adaptation to the pandemic situation by increasing the implementation of 'CHSE' including Cleanliness, Health, Safety, Environment, and Collaboration; (2) Community development by integrating multicultural-oriented education in the coastal tourism and fisheries sector; (3) The Indonesian people reorient the halal tourism movement and sharia travel, government regulations and the role of Islamic organizations to support the development of halal tourism and sharia travel.